Digitalization Of The Board Of Commissioners Supervision Program Through The Application Of Good Corporate Governance Principles - Mohamad Fajri Mekka Putra; Sihabudin Sihabudin; Budi Santoso; Reka Dewantara (Cita Konsultindo Research Center, 2023)
Company management in accordance with the Good Corporate Governance (GCG) principles can actualize good implementation of the duties and functions of every organ in the Company complying with the articles of association governing them. The Company's organs consist of the General Meeting of Shareholders (GMS), the Board of Commissioners (BOC), and the Board of Directors (BOD). BOC holds a fiduciary duty which in its entirety holds the supervisory function, and acts as an advisor to the BOD of the Company. The implementation of BOC’s positions must be based on the best interests of the Company and not intended for personal interests. Currently, supervision on the implementation of BOC’s positions which has been carried out manually so far is considered less than optimal due to the fact that there are still many cases of BOC carrying out their positions contradicting with the laws and regulations, causing material and immaterial losses to the Company. The implementation of GCG principles can facilitate the supervision of the BOC’s position and avoid abuse of authority of BOC’s position, but in fact the implantation of GCG principles has not been implemented properly by companies. Digitization of BOC’s supervisory program through the implementation of GCG principles in Company’s management by the BOD is considered the right solution to overcome these legal matters. Therefore, legal issues raised and analyzed in this study includes the implementation of GCG digitization associated with the supervision program on the implementation of BOC’s positions by the BOD in gaining Company’s legal benefits, and regulatory reformulation regarding GCG digitization program implemented in supervising the BOC’s positions based on the prevailing regulations in Indonesia. This study uses a normative juridical analysis method through a statutory approach and prescriptive analysis techniques. The concluded analysis results that digitizing the application of GCG principles related to supervising the BOC’s position makes it easier for the BOD to provide tighter supervision in actualizing Company’s legal benefit. Implementation on the digitization of GCG program is realized through advanced technology while still complying to Indonesian prevailing laws. Regulatory reformulation by the Government regarding BOC’s supervision digitization program must refer to the 5 (five) principles of GCG, the Electronic Information and Transactions Law, the Company Law, and the Job Creation Law in Indonesia. The regulation shall comply the existence of a special supervisory agency in charge of overseeing the implementation of GCG principles regarding Company’s digital supervision program on BOC’s positions by BOD.